2021
DOI: 10.1016/j.aprim.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida en personas con depresión y comorbilidad física desde una perspectiva de género

Abstract: Objetivo El objetivo del estudio es describir la percepción de la calidad de vida relacionada con la salud de personas con depresión y comorbilidad física bajo una perspectiva de género. Se incluyeron 380 individuos mayores de 49 años con, al menos, una patología de las siguientes: diabetes, enfermedad obstructiva pulmonar crónica y cardiopatía isquémica, reclutadas en 31 equipos de atención primaria de Cataluña. La calidad de vida se midió con la escala EuroQol (EQ-5D). Además, se recogieron vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…In our findings, women had an almost 3-fold higher risk of having poor HRQoL. It has been reported that women with diabetes tend to be more affected in HRQoL dimensions compared to men 24 . Gender-specific care strategies should be considered for patients with diabetes for better disease management and, consequently, improved HRQoL for both men and women.…”
Section: Discussionsupporting
confidence: 59%
“…In our findings, women had an almost 3-fold higher risk of having poor HRQoL. It has been reported that women with diabetes tend to be more affected in HRQoL dimensions compared to men 24 . Gender-specific care strategies should be considered for patients with diabetes for better disease management and, consequently, improved HRQoL for both men and women.…”
Section: Discussionsupporting
confidence: 59%
“…En nuestros hallazgos, las mujeres presentaron un riesgo casi tres veces mayor de tener una pobre CVRS. Se ha reportado previamente que son las mujeres con diabetes las que ven más afectadas las dimensiones de la CVRS, en comparación con los hombres 24 . Se requiere considerar las estrategias de atención en los pacientes con diabetes considerando aspectos de género, que permitan alcanzar un mejor cuidado de la enfermedad y por lo tanto una mejor CVRS tanto en hombres como en mujeres.…”
Section: Discussionunclassified
“…Second, we establish two components to compute differences between CFLE and LEWC: differences based on mortality (longevity) and differences based on morbidity (prevalence). To establish the contribution of each component, we relied on a generalized decomposition technique (Nusselder & Looman, 2004 ; van Raalte & Nepomuceno, 2020 ). The decomposition can be applied to different moments for a given population (considering compositional changes over time), or to two populations at a single moment (considering different compositions between compared groups).…”
Section: Methodsmentioning
confidence: 99%
“…The decomposition can be applied to different moments for a given population (considering compositional changes over time), or to two populations at a single moment (considering different compositions between compared groups). Such techniques identify the contribution of morbidity and mortality components (Andreev et al, 2002 ; van Raalte & Nepomuceno, 2020 ), allowing us to appropriately determine the role of each one in the obtained difference in two health expectancies, and which age groups are the ones that concentrate such contributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation